Kosovo Country Economic Memorandum, November 2021 : Raising Agricultural Productivity - World Bank (World Bank, Washington, DC, 2022)
Igniting farm productivity can support growth and job creation in Kosovo. Agricultural production, in real terms, has been decreasing in Kosovo since 2009 but employment has not changed much. This note examines drivers of agricultural productivity and its growth in Kosovo, and implied constraints on growth of agriculture, using farm-level data. The results of the productivity analysis suggest that in Kosovo there is a considerable misallocation of resources that if remedied can boost growth and job creation. In Kosovo, which suffers from low technical efficiency (TE), an average farm can produce the same amount of output using 72.8 percent less inputs. For micro and small farms, the current design of farm support does not facilitate income smoothing. On the other hand, agribusiness, mainly food processing, has been growing steadily in terms of number of firms, annual turnover, and employment. Finally, the impacts of Coronavirus disease 2019 (COVID-19) on Kosovo agriculture have been multiple and so have been policy responses.